Business Process Analysis on VWX Platform Using Deming's Cycle - Anindo Saka Fitri; Ningrum, Dea Kusuma; Purwitasari, Astri; Araf O., Monica Exsanni; Ismawardi, Alya Maytsa (Jurnal Mebis, 2024)
This study focuses on analyzing and improving the business processes of the VWX platform, a major player in the online travel industry. By utilizing Deming's Plan-Do-Check-Act (PDCA) cycle, this research aims to propose a new business process for the VWX platform especially inefficiencies in the refund process, one of the platform's critical service areas. Through tools such as Fishbone Diagram and Cross-Functional Flowchart (CFF), several issues were identified, including system automation gaps, unclear refund policies, and delays in processing due to third-party integrations. To address these issues, the study proposes automated refund systems, clearer refund guidelines, and enhanced customer service training. Additionally, the implementation of real-time notifications and system upgrades is recommended to improve process transparency and user satisfaction. The findings suggest that by adopting these improvements, VWX can significantly enhance operational efficiency, reduce customer complaints, and remain competitive in the digital travel marketplace. This research contributes valuable insights into how continuous process improvement methodologies like PDCA can be applied to optimize digital service platforms.